If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 15xz + -4y = 0 Solving 15xz + -4y = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '4y' to each side of the equation. 15xz + -4y + 4y = 0 + 4y Combine like terms: -4y + 4y = 0 15xz + 0 = 0 + 4y 15xz = 0 + 4y Remove the zero: 15xz = 4y Divide each side by '15z'. x = 0.2666666667yz-1 Simplifying x = 0.2666666667yz-1
| 6(p)+4=68 | | (X-4)^3/4 | | -13=7+f | | 5c-10=25 | | (x-4)*7=32 | | 15x^3-20x^5= | | x-4*7=32 | | C+5=-12 | | 5x^4-16x^2+3=0 | | 74=4t+10 | | n*6=80 | | 36=j+13 | | 8y=-10 | | 50+x+30-2=y | | 8+2(x+4)= | | 5n-8=-8 | | (X-5)*8=72 | | (1/2)/(3/5) | | 45*4/9 | | x+35=4 | | (-64)^-2/3 | | 2(7x+7y)=2(-35) | | x^5+5x-36x=0 | | 9(y-2)=8y-6 | | (9x-6w)+(4x+8y)+(4y+4w)= | | -7(2x+2y)=-7(-10) | | n*5=20 | | 0=5p^2+240p-160 | | b/6+3=6 | | X^2+18x+81=21 | | n+10=25 | | 9+d^4=23 |